2018
DOI: 10.3389/fimmu.2018.01722
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Resident Memory T Cells for Cancer Immunotherapy

Abstract: A novel population of memory CD8+ T cells called resident memory T cells (TRM) has been identified based on their phenotype (CD103, CD69) and on their local tissue residency without recirculating in the blood. These cells have been implicated in protective immune response against pathogens in both animal models and humans. Their role in cancer is just emerging as a key player in tumor immunosurveillance. Many properties of these cells suggest that they could control tumor growth: (i) they respond much faster t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 57 publications
(94 reference statements)
0
39
0
Order By: Relevance
“…T RM are characterized by CD69 and CD103 expression, respond faster to antigen re-exposure and have a superior cytotoxic capacity than other types of memory T cells (10,326). In the clinical arena, using memory CTLs instead of naïve or effector CTLs holds promise for an improved and longlasting anti-tumor effect that locally protects from recurrence (10,57).…”
Section: Iiii the Adaptive Immune System In Cancermentioning
confidence: 99%
“…T RM are characterized by CD69 and CD103 expression, respond faster to antigen re-exposure and have a superior cytotoxic capacity than other types of memory T cells (10,326). In the clinical arena, using memory CTLs instead of naïve or effector CTLs holds promise for an improved and longlasting anti-tumor effect that locally protects from recurrence (10,57).…”
Section: Iiii the Adaptive Immune System In Cancermentioning
confidence: 99%
“…In recent years, immune checkpoint blockade has demonstrated that targeting the immune system by activating previously exhausted or dysfunctional T cells can lead to long-term control of various cancers, including melanoma ( 57 59 ). In particular, cytotoxic CD8+ T cells are important for tumor cell killing and memory CD8+ T cells are important for durable anti-tumor immunity ( 60 ). However, many tumors, including neuroblastoma and other pediatric tumors, do not respond or have limited response to CTLA-4 and PD-1/Programmed death-ligand 1 (PD-L1) blockade ( 32 , 33 ), and studies have found mechanisms of resistance, including poor infiltration of T cells, tumor cells that lack response to interferon-γ (IFN-γ), and immunosuppressive cell populations in the tumor microenvironment ( 61 ).…”
Section: Tumor Microenvironment Of Neuroblastomamentioning
confidence: 99%
“…T RM cells were quantified using quantitative multiplex immunofluorescence staining to show that the presence of T RM cells in immunotherapy-naïve melanoma samples was associated with significantly increased melanoma-specific survival, and this cell population was further expanded using anti-PD-1 therapy [23]. Additionally, Blanc et al showed that the T RM cell population increases within tumors during the early stages of anti-PD-1 treatment [41]. In addition, T RM cells isolated from lung carcinomas co-cultured with autologous tumor cells demonstrate enhanced cytotoxic activity in the presence of PD-1 targeting antibodies compared to those not treated with PD-1 antibodies [9].…”
Section: Function Of T Rm Cells In Cancermentioning
confidence: 99%